Профессор А.И. Уткин: страницы биографии классика истории и политологии международных отношений - Пашковский, П.И. (Культура народов Причерноморья, 2014)
Рассмотрены основные этапы биографии выдающегося российского учёногомеждународника, специалиста в области внешней политики США, истории и теории международных отношений, геополитики, всемирной истории нового и новейшего времени, автора более 70 монографий и нескольких сотен статей в отечественных и зарубежных изданиях, доктора исторических наук, профессора А.И.Уткина. Представлены наиболее значимые сюжеты из жизни исследователя. Охарактеризованы его научные достижения. Розглянуто основні етапи біографії видатного російського вченого-міжнародника, фахівця в галузі зовнішньої політики США, історії та теорії міжнародних відносин, геополітики, всесвітньої історії нового та новітнього часу, автора більше 70 монографій і декількох сотень статей у вітчизняних і зарубіжних виданнях, доктора історичних наук, професора А.І.Уткіна. Подано найбільш значущі сюжети з життя дослідника. Охарактеризовано його наукові досягнення. The main stages of the biography of the outstanding Russian scientist, of an expert on international relations, of a recognized specialist in the field of the US foreign policy, history and theory of international relations, geopolitics, global history of modern and contemporary, of the author of more than 70 books and several hundred articles in domestic and foreign editions, of doctor of historical sciences, of professor A.I. Utkin have been considered on the basis of an extensive of the source base and historiography. The most significant stories from the life of the researcher have been presented. His scientific achievements have been characterized. Inventory of main works of the scientist has been specified. Excerpts from the memoirs of his contemporaries have been presented. The views of experts in the history and theory of international relations have been highlighted. It is proved that currently A.I.Utkin continues to remain one of the most authoritative Russian researchers in the world. Relevance and scientific value of his works will only grow over the years.